Optimal temperature profile in methanol synthesis reactor - Jahanmiri, A.; Eslamloueyan, R. (Chemical engineering communications, 2002)
An optimal temperature profile is determined for a methanol synthesis reactor of LURGI type. The temperature profile is estimated so that methanol production rate in the reactor outlet will be maximized. First, the reactor is simulated based on heterogeneous one- and two-dimensional models. The comparison of the simulation results and plant data shows that the heterogeneous one-dimensional model can reliably be used for determining optimal temperature profile. Since optimal temperature profile for reversible exothermic reaction in tubular reactors is a decreasing function of reactor length, the technique of control variable parameterization is used for determining optimal temperature profile in a methanol reactor. In this way, a third order polynomial is considered for the temperature profile and the polynomial coefficients are as decision variables. The optimization is based on a Quasi-Newton's method (BFS technique), and the objective function is methanol flow rate at the reactor outlet. The results of optimization indicate that if optimal temperature profile is implemented in the reactor, methanol production will significantly be increased.